Advances in technical methods and applications of subretinal injections in experimental animals - Song, Chunyan; Ji, Yuke; Wang, Yun; Yang, Weihua (Frontiers in Veterinary Science, 2025)
The subretinal injection technique is an important intraocular drug delivery modality that allows access to the subretinal space to directly act on target cells or the administration of medications, markedly improving the therapeutic efficacy of ocular diseases. Subretinal injection in experimental animals is a commonly used manipulation method for investigating vitreoretinal diseases, particularly when gene therapy and cell therapy studies are involved. In this study, we conducted a systematic review on the injection methods, operation sites, post-injection indicators, as well as the progress and significance of subretinal injection in experimental animals, discussed and compared the advantages and disadvantages of the subretinal injection technique, summarized its specific application of subretinal injection in experimental animals, and explored the development and application of this new technology of subretinal injection, hoping to offer insights that may facilitate the further development of this technology.